Desfile de moda nos espaços da cidade: abordagem semiótica dos regimes de visibilidade, de identidade, de interação e de sentido - Souza, Josenilde Silva (2011)
This work analyzes to what extent the choice of a certain city space for the performance of fashion shows is decisive to establish a new plastic and semantic configuration. In the transition of the conventional space formed by an indoor room to an outdoor and unconventional space for example, a viaduct, a street or a garden we investigate the fashion show s ways of organizations in different spaces and in what ways they modify their structuring and at the same time they redefine the city. In these modalities organizations the parameters of public and private spaces significantly intervene as much as the engagements of these poles with the basic category open vs. closed space. The narrative semiotics of Algirdas Julien Greimas and the postulations of Eric Landowski are the theoretical and methodological frameworks used to handle the problem of how the presence modes of the fashion show in the urban space act in the production of visuality, visibility and identity, as well as on the performances communicative and interactive processes. A set of fashion shows was analyzed from the hypothesis: 1) the fashion shows compose syncretic processes that articulate heterogeneous languages distinctly in order to generate communicational developments promoted by the aesthetic arrangement of the expression plan by accomplishing the semantic investments of the content; 2) the discursive constructions build new visuality, visibility and identity modes of the fashion creators and their brands; 3) the city places unfolds produce sensible and intelligible apprehensions in the public inserted in the discourse and 4) these enunciative choices define the identity of the fashion creator and the brand, as much as its user and the city. Photographic records of the researcher outlined the imagetic corpus of four fashion shows observed in the period between 2005 and 2010: Maria Garcia (SPFW Winter/2010), Cavalera (SPFW Summer/2010), Fashion Mob (Casa dos Criadores/2010) and Karla Girotto (Fashion Rio, Summer/2005). The object of this research results from the researcher s direct observation of the performances, highlighting the criteria for analysis - the experience of aesthetic and aesthesic order that the types of interaction produced in the spaces build among brand, fashion creator and public. The analytical conclusion allowed the elaboration of four description categories and the analysis of this construction that make the fashion show, the creator and the brand exist, which will be able to be reoperated in other communicational processes